Evaluation of Clinacanthus nutans(Burm. f.) Lindau and Ficus deltoidea leaf extracts for cartilage and bone marrow health in experimental rat osteoarthritis - Che Ahmad Tantowi, Nur Adeelah (2016)
Medicinal plants have been used to treat various ailments including in osteoarthritis (OA) for decades. Currently, the existing drugs for treating OA only alleviate symptoms and improve the joint function, but cannot treat cartilage and bone damage. Developing therapeutics from plant-derived sources may exert less negative side effects, compared to the use of common non-streroidal anti-inflammatory drugs (NSAIDs) for osteoarthritis. Hereby, the present study investigated the effect of Clinacanthus nutans (belalai gajah) and Ficus deltoidea (mas cotek), compared with diclofenac, on cartilage and bone marrow health on experimental OA model. In preliminary in vitro bovine cartilage explant culture, the recombinant bovine IL-1β of 10 ng/mL was added to the cartilage explants in DMEM/F12 media to induce OA condition. CN or FD leaf extracts at 20, 40, and 80 μg/mL, or diclofenac at 5 μg/mL, were simultaneously added into the medium after IL-1β induction. The amount of proteoglycan loss, reactive oxygen species (ROS) produced, and chondrocytes morphology were evaluated. In in vivo experiment, 42 12-week-old Sprague Dawley female rats were randomized into seven groups (n=7). The rats were subjected to bilateral ovariectomy (OVX) and OA was induced by intra-articular injection of monosodium iodoacetate (MIA) at 60 mg/mL into right knee joints, excluding healthy group. Healthy and OA non-treated groups were given deionized water while treatment groups were orally treated with 200 or 400 mg/kg body weight of CN or FD leaf extracts or 5 mg/kg body weight of diclofenac once a day for 28 days. Serum levels of inflammation including interleukin 1 beta (IL-1β), interleukin 6 (IL-6), and prostaglandin E2 (PGE2); cartilage catabolic including matrix metalloproteinase 1 (MMP-1), matrix metalloproteinase 13 (MMP-13), C-terminal cross-linked telopeptide of type II collagen (CTX-II), and N-terminal propeptide of collagen type II (PIINP); and bone turnover markers including osteoprotegerin, osteocalcin, receptor activator of nuclear kappa-beta ligand (RANKL), and C-terminal crosslinked telopeptide type I collagen (CTX-I) were assessed by enzyme-linked immunosorbent assay (ELISA). Articular cartilage changes were determined by radiological, macroscopic, and histological observations. Gene expressions of inflammatory including nuclear factor kappa beta (NF-κβ), interleukin 1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), cyclooxygenase 2 (COX-2), and prostaglandin E2 (PGE2); and cartilage catabolic mediators including matrix metalloproteinase 1 (MMP-1), matrix metalloproteinase 13 (MMP-13), A disintegrin and metalloproteinase with thrombospondin motifs 4 (ADAMTS-4), and A disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS-5) were determined to study the mechanisms involved. Bone turnover regulations were evaluated via bone mass density, dimension, biomechanics, and microarchitecture. Flavones of apigenin derivatives including vitexin, isovitexin, schaftoside, and isoschaftoside were identified in both CN and FD leaf extracts. Preliminary in vitro study showed chondroprotective effects of CN and FD leaf extracts and diclofenac by significantly inhibiting proteoglycan loss, ROS production, and preventing chondrocytes apoptosis. In in vivo study, CN and FD leaf extracts possessed cartilage and bone protecting nature by significantly suppressing the augmented activities of inflammatory (IL-1β, IL-6, and PGE2), and cartilage catabolic (MMP-1 and MMP-13) serum levels comparable to diclofenac. The osteoarthritic rats treated with the extracts and diclofenac showed significant reduction of cartilage erosion via radiological, macroscopic and histological images, compared to untreated osteoarthritic rats. The extracts significantly down-regulated NF-κβ, IL-1β, TNF-α, IL-6, PGE2, MMP-1, and MMP-13 expressions in the osteoarthritic cartilage similar to diclofenac. Furthermore, CN and FD leaf extracts administration protected bone marrow by significantly increased bone volume ratio, decreased trabecular separation, and decreased total porosity of the bone marrow. These findings were supported by bone turnover markers; which the extracts significantly increased bone formation (osteoprotegerin and osteocalcin) and reduced bone resorption (CTX-I and RANKL) markers, comparable to diclofenac. Overall, CN and FD leaf extracts were demonstrated to be a potent agent mitigating cartilage and bone loss in OA. The results achieved were at least as good than those with diclofenac, a widely used NSAID and a benchmark pharmacological treatment for OA. The main bioactive compounds are probably responsible for anti-inflammatory and antioxidant properties in the protection of cartilage and bone marrow in OA.